Pursuing Deep Equity in "Blended" Classrooms: Exploring the In-Person Teacher Role in Supporting Low-Income Youth through Computer-Based Learning. Issue 5 (May 2019) - Pollock, Mica; Yonezawa, Susan; Gay, Hilary; Rodriguez, Lilia
Background/Context: Efforts to increase low-income, underrepresented students' access to coursework increasingly tap computer-based course materials. Yet as we turn increasingly to computers for instruction, what might the in-person teacher still be needed to do? This paper presents seven in-person "teacher roles" that precollege low-income youth and their teachers deemed necessary for supporting students as they used computer-based materials. Data were collected across two years in 19 summer school classrooms where 400 high school students took computer-based college-preparatory courses supported in person by teachers and teachers' assistants (TAs). We offer an empirically informed conceptual framework supporting next research on (and innovation of) equity-minded "blended" classroom practice. We define "equity" effort as active effort to meet the needs of each student and all groups of students; here, the effort was to sufficiently prepare each and all students for college. Purpose/Objective/Research Question/Focus of Study: We used focus groups, classroom observations, and interviews to study the roles that teachers embraced and students valued. We asked two research questions: (1) How do in-class teachers (teachers and TAs) support students as students access material online? (2) According to student and adult participants, which teacher supports are key to student success in the courses? Research Design: Researchers observed classrooms to capture patterns of frequently repeated adult-student and peer interaction. Through informal and semi-structured ethnographic interviews and focus groups, we invited participants to comment on needed supports for classrooms and on the supports they saw as particularly valuable (or not). We conducted approximately 46 hours of interviews and focus groups and 500 hours of observation. Conclusions/Recommendations: We describe three in-person teacher roles that participants said assisted students in achieving basic equity with computer materials—that is, precollege content access and course credit otherwise denied. We explore four in-person teacher roles that participants called particularly necessary for deep equity—to support students' individual and collective comprehension of the online materials, often through dialogue. We conclude that the teacher's overarching role for achieving equity in these blended classrooms was to continually adjust pedagogy as needed to ensure each and all students both accessed and understood the precollege content. This suggests that adding technology to classrooms to support all students fundamentally requires teachers.